Strategi Pengembangan Wisata Menara Kudus Berbasis Kearifan Lokal sebagai Upaya Pemulihan Ekonomi Masyarakat - Nanang Dwi Praatmana; Muhammad Arsyad (Academic Journal of Da'wa and Communication, 2022)
The existence of tourist objects as one of the pillars of the community's economy during the pandemic is decreasing. Along with the increasing number of Covid cases in Indonesia, several tourist attractions were closed due to the PPKM. The research aims to formulate alternative strategies that can be implemented in the development of the Menara Kudus tourist attraction during the pandemic. This is descriptive research with primary data sources consisting of observations and questionnaires. Technical sampling was chosen non probability sampling, because Menara Kudus is one of the popular tourist attractions in Kudus and offers a tourism concept that combines religion and culture. The analytical method used is SWOT. The results show that the position of the Menara Kudus tourist attraction is in quadrant I, meaning that the Menara Kudus tourist attraction is in strong internal and external conditions. An alternative strategy that can be applied is to highlight local wisdom in the form of cultural celebrations whose implementation is carried out by implementing health protocols as the main tourist attraction, with the hope that the community's economy can bounce back after going through the pandemic.